Etiology of Hepatocellular Carcinoma: Special Focus on Fatty Liver Disease - Suresh, Diwakar; Srinivas, Akshatha N.; Kumar, Divya P. (Frontiers in Oncology, 2020)
Hepatocellular Carcinoma (HCC) is a highly aggressive cancer with mortality running parallel to its incidence and has limited therapeutic options. Chronic liver inflammation and injury contribute significantly to the development and progression of HCC. Several factors such as gender, age, ethnicity, and demographic regions increase the HCC incidence rates and the major risk factors are chronic infection with hepatitis B virus (HBV) or hepatitis C virus (HCV), carcinogens (food contaminants, tobacco smoking, and environmental toxins), and inherited diseases. In recent years evidence highlights the association of metabolic syndrome (diabetes and obesity), excessive alcohol consumption (alcoholic fatty liver disease), and high-calorie intake (nonalcoholic fatty liver disease) to be the prime causes for HCC in countries with a westernized sedentary lifestyle. HCC predominantly occurs in the setting of chronic liver disease and cirrhosis (80%), however, 20% of the cases have been known in patients with non-cirrhotic liver. It is widely believed that there exist possible interactions between different etiological agents leading to the involvement of diverse mechanisms in the pathogenesis of HCC. Understanding the molecular mechanisms of HCC development and progression is imperative in developing effective targeted therapies to combat this deadly disease. Noteworthy, a detailed understanding of the risk factors is also critical to improve the screening, early detection, prevention, and management of HCC. Thus, this review recapitulates the etiology of HCC focusing especially on nonalcoholic fatty liver disease (NAFLD)- and alcoholic fatty liver disease (AFLD)-associated HCC.